Ishtar, her ‘strength’ and her iconographic proposal - degli Abbati , Valeria (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2025)
A naked goddess with crossed legs is depicted on some Near Eastern artefacts, mostly cylinder seals and seal impressions, dated for the largest part to the Late Bronze Age. Although there are many different and interesting interpretations of this character, here I would propose that this rare iconography may be the representation of the hypostasis of Ishtar named Agushaja and known from her own myth written during the Reign of Hammurabi of Babylon.